Perbandingan Model Pembelajaran Discovery Learning dan Talking Stick terhadap Hasil Belajar - Arifin, Zainal (JURNAL EDURELIGIA, 2018)
Based on the statement of the problem how the comparison of students learning out comes used Learning model Discovery Learning and Talking Stick. Cooperative Learning model Discovery Learning and Talking Stick are one of model that are usually used in the mathematic Learning the advantage of them are can stimulate the development ability to think creatively and comprehensive, and stimulate student in order to more achre study. The purpose of this research was to know what it is there or no the comparison cooperative learning model Discovery Learning and Talking Stick of learning out come. The kind of this research was quantitative research with using the true experimental design post-test only control design. Before The researcher analysis data, I used the normality test and homogeneity test hypothesis test in data’s analysis. From the analysis result obtained the average value of class that was given cooperative Learning model type Talking Stick (control class) was higher than average role of class that was given cooperative learning model Discovery Learning (experiment class) by using the 5% error test then obtained -0,74<1.68, so t count t-table. The conclusion Ho was accepted, it mean that there was comparison cooperative Learning model Discovery Learning and Talking Stick to learning outcome.